Human Enteric Pathogens in Eight Rivers Used as Rural Household Drinking Water Sources in the Northern Region of South Africa - Potgieter, Natasha (Int J Environ Res Public Health, 2020)
People living in rural areas still rely on the use of environmental water that is contaminated by human and animal activities. This study assessed the occurrence of human enteric pathogens in rivers that are used by rural communities Vhembe District of South Africa as a source of drinking water covering two seasons (winter and summer) over a one-year period. Water quality was assessed using physico characteristics and indicator organisms (total coliforms, E. coli, Clostridium perfringens). Pathogens tested included bacteria (Pathogenic E. coli, Salmonella-, Shigella- and Vibrio spp.), protozoa (Cryptosporidium- and Giardia spp.), and enteric viruses (Rota-, Noro-, Entero-, and Adenoviruses) while using published molecular protocols. The results showed that the indicator bacteria counts exceeded South African drinking water quality guideline limits and pathogenic E. coli was detected in the samples. No Shigella spp. were isolated, while Vibrio spp. and Salmonella spp. were present; parasites were detected in four rivers and Enteric viruses were predominantly detected in the winter season. The results indicated the poor condition of water and the potential health risks to consumers highlighting the need for implementing river catchment management strategies for continued sustainability in these rivers.